2018
DOI: 10.1037/abn0000375
|View full text |Cite
|
Sign up to set email alerts
|

Clinical differentiation of sluggish cognitive tempo and attention-deficit/hyperactivity disorder in children.

Abstract: This study (1) determined if clinical elevations of sluggish cognitive tempo (SCT) and attention-deficit/hyperactivity disorder (ADHD) symptom distributions in a large community sample of children would allow for identifying separate SCT only, ADHD only, and SCT+ADHD clinical groups, (2) examined co-occurrence of clinically elevated SCT and ADHD, (3) evaluated whether these clinical groups differed in their gender distribution, co-occurring mental health symptoms, and impairment in academic and social function… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
59
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 89 publications
(62 citation statements)
references
References 42 publications
2
59
1
Order By: Relevance
“…However, in contrast to our hypotheses, male sex was not associated with SCT. The failure to find sex differences in SCT is consistent with multiple studies that do not report sex differences for SCT (Barkley, 2012; Becker & Langberg, 2013; Carlson & Mann, 2002; Jarrett, Rapport, Rondon, & Becker, 2014; Marshall et al, 2014; Servera et al, 2018). Notably, participants in these studies were all drawn from community or school-based samples with two exceptions (Marshall et al, 2014).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…However, in contrast to our hypotheses, male sex was not associated with SCT. The failure to find sex differences in SCT is consistent with multiple studies that do not report sex differences for SCT (Barkley, 2012; Becker & Langberg, 2013; Carlson & Mann, 2002; Jarrett, Rapport, Rondon, & Becker, 2014; Marshall et al, 2014; Servera et al, 2018). Notably, participants in these studies were all drawn from community or school-based samples with two exceptions (Marshall et al, 2014).…”
Section: Discussionsupporting
confidence: 81%
“…However, SCT does not appear to indicate a subtype of ADHD (Barkley, 2012, 2013; Becker, Marshall, McBurnett, 2014; Becker et al, 2016; Willcutt et al, 2012). Instead, researchers have increasingly examined SCT as a separate construct in community and clinical samples (Becker, Luebbe, Fite, Stoppelbein, & Greening, 2014; Becker, Burns, Schmitt, Epstein, & Tamm, 2019; Leopold et al, 2016; Servera, Sáez, Burns, & Becker, 2018). These efforts have suggested that SCT may be a construct of transdiagnostic importance (Becker & Willcutt, 2019) or its own mental disorder (Barkley, 2013, 2014).…”
mentioning
confidence: 99%
“…Further, in contrast to ADHD inattention, there is emerging evidence that youth can provide valid self-reports of their own SCT symptoms 36,40 and we found sleep restriction to worsen SCT across both parent and adolescent ratings. These multi-informant effects are important since it is estimated that 25-40% of youth with ADHD also have elevated SCT symptoms 41,42 and SCT symptoms are themselves linked to a range of functional impairments such as social withdrawal and internalizing psychopathology. 18 Consistent with other studies, 8,15,16 parents did not report greater hyperactivity-impulsivity during sleep restriction compared to sleep extension.…”
Section: Discussionmentioning
confidence: 99%
“…That is, SCT and ADHD-IN are strongly correlated empirically (Becker et al, 2016) and also overlap clinically (Barkley, 2012). The picture grows even more complex when also considering the clinical overlap of SCT and ADHD with internalizing symptoms such as depression (Servera et al, 2018). It is thus somewhat difficult to know what the nature of SCT is when both ADHD and internalizing symptoms are partialled out.…”
Section: Discussionmentioning
confidence: 99%